SOCIALIZATION AND GUIDANCE IN THE MAKING OF HERBAL SAUNAS IN ALUE DEAH TEUNGOH VILLAGE IN 2025 - Tahara Dilla Santi; Aditya Candra; Naimah; Ika Waraztuty; Andri; Said Aandy Saida; Ns. Eka Oktarina Riani (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
The International Labor Organization (ILO) reports that 2 million people die in the workplace, one of the causes being overexertion. Herbal saunas are decoctions of plants with medicinal properties, including anti-fatigue. Warm steam applied to the skin helps dilate blood vessels, improving circulation. The purpose of this activity was to provide knowledge about various medicinal plants that can be used as herbal saunas and to provide community members with skills in making herbal saunas. The PKM method involved participation through outreach and mentoring women in preparing herbal saunas. The activity took place on July 27, 2025, in Alue Deah Teungoh Village, with 15 women participating in the Family Welfare Movement (PKK). The activity began with a pre-test and then a herbal sauna booklet. The results of this activity were an increase in the knowledge and skills of the PKK women, demonstrated by the resulting product, a dried herbal sauna packaged in a standing pouch. Participants were very enthusiastic about the training. The activity concluded with the use of herbal saunas, which were boiled in a steamer and the steam flowed into a portable sauna tent. Participants took turns using the sauna, which had been filled with the herbal sauna decoction.